Simulation de l’emboutissage par approche inverse améliorée pour l’estimation du retour élastique - Ben-Elechi, Slim; Naceur, Hakim; Batoz, Jean-Louis (European Journal of Computational Mechanics, 2005)
In this paper we present an Improved Inverse Approach (IIA) for the stamping simulation. In the new version, the stresses due to bending and unbending effects are estimated analytically from the final workpiece, especially in the die entrance radii for curvature changes. The bending /unbending moments and the final shape are used to calculate springback using a second incremental Approach based on the Updated Lagrangian Formulation. Two tests proposed as benchmark for NUMISHEET’93 have been used to validate the method; good results on the prediction of springback have been obtained. The obtained results are validated using STAMPACK® and ABAQUS® industrial codes.